Digital Economic Literacy: Elevating Culinary Micro, Small and Medium Enterprises (MSMEs) with Digital Branding - Andre Noevi Rahmanto (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Digital Economy Literacy is a necessity for business people, but there is still a lack of information about technology, making it difficult for MSMEs to switch to digital business. Four factors make it difficult for MSMEs to go digital. MSMEs in the culinary field in these locations still do not master packaging, branding, marketing techniques, and internet technology, which is a prerequisite for online marketing. This study aims to see how MSMEs have digital economy literacy in that location. The method used in this research is a qualitative method with a Participatory Action Research (PAR) approach where researchers directly help the community through empowerment or service. Researchers carried out data collection techniques through observation and Focus Group Discussion (FGD). The results of this study are that MSME actors in the culinary field can carry out digital branding and online marketing techniques as a result of empowerment or community service by researchers, including 1) understanding digital tools that are considered the most accessible by MSME actors; 2) the assistance needed by MSMEs in digital appeals; and 3) the digital literacy level of MSMEs seen from the digital literacy competency model.